Expert System for Detecting Malnutrition in Toddlers Using the WEB-Based Certainty Factor Method - Fretty S Siahaan; Lili Tanti; Khairul Ummi (Trigin Publisher, 2023)
Malnutrition is based on the nutritional status indexes Weight Loss by Age (W / A) <-3 SD is severely underweight equivalent term. Where there are two types of malnutrition are kwashiorkor, marasmus. if the lack of nutrition the infants are susceptible to malnutrition because of the growth and development of this cycle requires nutrients were greater than the age of the other so easily suffer from nutritional disorders, if not treated immediately will cause death and chronic infection. In the current system there are some drawbacks such as the absence of security following safety features such as anti-virus as a means to protect the database on these weaknesses then designed and built an expert system Identifying Malnutrition In Toddlers with certainty factor method designed web- based using program based on Macromedia Dreamweaver 8, especially PHP and using MySQL as database. The report is designed using iReport and the modeling system is done with UML 2.0. design aims to build an expert system to identify symptoms of malnutrition using the method of Certainty Factor (CF) and to build an expert system that will generate information from experts (books, as well as references that support) accurately.